Analisis Tingkat Efisiensi Teknis Usahatani Kentang (Solanum Tuberosum) Di Provinsi Jawa Timur - Wahyu, Yanuar; Rosihan Asmara; Dwi Retno Andriani; Nuhfil Hanani; Fahriyah (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
This study aims to analyze the level of technical efficiency in potato farming (Solanum tuberosum) in East Java Province, using the Data Envelopment Analysis (DEA) approach. The research locations were selected in Sumber Brantas Village, Batu City, and Wonokerso Village, Probolinggo Regency, involving 120 potato farmers as respondents. The analysis results indicate that the majority of respondent farmers are in the Increasing Return to Scale (IRS) production scale, with 36 farmers, or about 30% of the total respondents, being in a Constant Returns to Scale (CRS) condition, which indicates that they are at a relatively optimal efficiency level, with 71 farmers, or approximately 59.17% of the total respondents, achieving an efficient score of 1.00. On the other hand, there are 13 farmers, or about 10.83% of the total respondents, who are in a Decreasing Return to Scale (DRS) production scale. The average technical efficiency of potato farmers in this study reached 81.2%, with a percentage of 48.33%. Most farmers from the total respondents successfully achieved an efficient value with a score of 1.00. However, there are also two farmers categorized as having very low efficiency at 1.67%. Meanwhile, the percentage of low efficiency is 11.67%, moderate efficiency is 22.50%, and high efficiency is 15.83%, indicating significant potential for improvement. These findings suggest that inefficiency is caused by suboptimal input management and the need for training and guidance to enhance farmers' understanding of better cultivation practices. Therefore, this study recommends interventions in agricultural input management and increased access to technology, capital, and infrastructure support as strategic steps to improve the overall technical efficiency of potato farming